Synergistic photothermal cancer immunotherapy by Cas9 ribonucleoprotein-based copper sulfide nanotherapeutic platform targeting PTPN2. (December 2021) - Yan, Tao; Yang, Kaiyong; Chen, Chao; Zhou, Zhiruo; Shen, Peiliang; Jia, Yuanyuan; Xue, Yu; Zhang, Zhenyu; Shen, Xu; Han, Xin
Abstract: Photothermal therapy (PTT) is a promising strategy for the treatment of advanced malignant neoplasm. However, the anti-tumor efficacy by PTT alone is insufficient to control tumor growth and metastasis. Here, we report a multifunctional nanotherapeutic system exerting a combined PTT and immunotherapy to synergistically enhance the therapeutic effect on melanoma. In particular, we selected the semiconductor nanomaterial copper sulfide (CuS), which served not only as a near-infrared (NIR) light-triggered photothermal converter for tumor hyperthermia but as a basic carrier to modify Cas9 ribonucleoprotein targeting PTPN2 on its surface. Efficient PTPN2 depletion was observed after the treatment of CuS-RNP@PEI nanoparticles, which caused the accumulation of intratumoral infiltrating CD8 T lymphocytes in tumor-bearing mice and upregulated the expression levels of IFN-ᵧ and TNF-α in tumor tissue, thus sensitizing tumors to immunotherapy. In addition, the effect worked synergistically with tumor ablation and immunogenic cell death (ICD) induced by PTT to amplify anti-tumor efficacy. Taken together, this exogenously controlled method provides a simple and effective treatment option for advanced malignant neoplasm. Graphical abstract: Yan et al. report a synergistic photothermal cancer immunotherapy strategy based on NIR light-triggered thermo-responsive CuS nanotherapeutic platform to deliver Cas9 ribonucleoprotein targeting PTPN2. The PTPN2 targeted immunotherapy provided a potential strategy to synergistically combine with immunogenic cell death (ICD) induced by PTT for the enhancement of anti-tumor immunity. Significant synergistic therapy efficacy was observed in vivo, suggesting the effectiveness of the exogenously controlled method in the treatment of advanced malignant neoplasm. Image 1 Highlights: NIR light triggered-CuS-RNP@PEI for efficient PTPN2 depletion and tumor hyperthermia. Synergistic effects of CuS-based PTT and PTPN2 targeted immunotherapy. PTPN2 KO reinforce immune microenvironment with immunogenic cell death effects. NIR light triggered synergistic photothermal cancer immunotherapy via CuS-RNP@PEI.